DUKUNGAN MASYARAKAT TERHADAP PERENCANAAN REHABILITASI HUTAN DIWILAYAH KESATUAN PENGELOLAAN HUTAN (KPH) KULAWI DI DESA WAWUJAI KECAMATAN MARAWOLA BARAT KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Palumpun, Kristianto; Dg Massiri, Sudirman; Anwar, Anwar; Maiwa, Arman (Universitas Tadulako, 2020)
In planning forest rehabilitation, support is needed so that the process of implementing forest rehabilitation can run well, rehabilitation of forests and land RHL has a major influence on the condition of the surrounding area because the purpose of forest and land rehabilitation is to improve, restore and restore the condition of damaged forests so that they can function with both as a regulator of water governance. The purpose of this study is to describe the forest rehabilitation planning process, andÂ find out community support in forest rehabilitation planning. This research was conducted for 2 months from August to September 2019 in Wawujai Village, Marawola Barat District, Sigi Regency, Central Sulawesi Province. The method in this Paeneltian uses descriptive research methods using primary data and secondary data as the type and source of data, at the data collection stage the data collection techniques used were interviews with 100 respondents of household heads who deliberately chose Purposive Sampling. From the results of the study found the characteristics of respondents consisted of education, employment, income for the rehabilitation plan of the forest area to be rehabilitated covering 50 hectares, 80 percent of respondents were supported and 20 respondents did not support forest rehabilitation planning.Keywords :Community support,planning,forest rehabilitation